Cryptic diversity and unexpected evolutionary patterns in the meadow lizard, Darevskia praticola (Eversmann, 1834). Issue 2 (3rd March 2016) - Freitas, Susana; Vavakou, Anna; Arakelyan, Marine; Drovetski, Sergei V.; Crnobrnja-isailović, Jelka; Kidov, Artem A.; Cogălniceanu, Dan; Corti, Claudia; Lymberakis, Petros; Harris, D. James; Carretero, Miguel A.
Abstract : Darevskia praticola differs from the other species of the genus in having a large but disjunct distribution, covering the Balkan and the Caucasus regions. Furthermore, most Darevskia species occupy saxicolous habitats, whereas D. praticola inhabits meadows and forest environments. Here we determine the phylogeographic and phylogenetic relationships of Darevskia praticola sensu lato and evaluate the current, morphology-based taxonomy. We sequenced two mtDNA genes (Cyt- b and ND4) and two nuclear loci (MC1R and RELN) for samples collected across the species range. Because our sequences amplified with the Cyt- b primers appear to represent a nuclear pseudogene we excluded this marker from the final analysis. Our results support monophyly of D. praticola and show its division into three clades. The first divergence, dated to the Late Pliocene, is between the Balkans and the Caucasus. The Caucasus lineage is further subdivided in a western Greater Caucasus and a Transcaucasia clade, likely due to subsequent differentiation during the Pleistocene. Our findings do not support the current taxonomic arrangement within D. praticola . The main geographic divergence likely happened due to a vicariance event associated with Plio-Pleistocene climatic and vegetation oscillations.